2009
DOI: 10.1177/019874290903500102
|View full text |Cite
|
Sign up to set email alerts
|

Persuading Students with Emotional Disabilities to Write Fluently

Abstract: A multiple-baseline design study was conducted to evaluate the effectiveness of strategy instruction in persuasive writing with eighth-grade students who attended a public day school for students with severe emotional and behavior disabilities. Students were taught to plan and write persuasive essays using the Self-Regulated Strategy Development model. Following mastery of the strategy, students were taught to apply the learned strategy to write fluently in 10 min. After more than 4 months of instruction, find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 17 publications
(17 reference statements)
5
41
0
Order By: Relevance
“…This is evidence that further supports that students in the experimental condition learned the strategy. These results replicated previous findings that have shown students who learn how to use the POWCTREE strategy are able to recall all parts (Mason & Shriner, 2008;Mastropieri et al, 2009Mastropieri et al, , 2010. In this study, SRSD procedures were effective to teach POWCTREE when used by classroom teachers to teach middle school students from a separate school setting for students with EBD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is evidence that further supports that students in the experimental condition learned the strategy. These results replicated previous findings that have shown students who learn how to use the POWCTREE strategy are able to recall all parts (Mason & Shriner, 2008;Mastropieri et al, 2009Mastropieri et al, , 2010. In this study, SRSD procedures were effective to teach POWCTREE when used by classroom teachers to teach middle school students from a separate school setting for students with EBD.…”
Section: Discussionsupporting
confidence: 89%
“…These findings were similar to previous SRSD studies that have shown a decrease in performance during generalization when compared to pretests and post instruction (Adkins, 2005;Mason & Shriner, 2008;Mastropieri et al, 2009). Comparison group students again increased in number of words and transition words written at generalization when compared to other time measures such as pre-and posttest, but this increase was not statistically significant in comparison to the performance of experimental students.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using this procedure, 90% of posttreatment points exceeding the extreme baseline value indicated a very effective treatment, 70% to 90% an effective treatment, 50% to 70% a questionable treatment, and less than 50% an ineffective treatment. This type of analysis was used in this intervention as it is commonly used in single-subject research utilizing the TREE intervention (Mastropieri et al, 2009) and has been proven to detect intervention effects (Campbell, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Strong effects were also found for single-subject studies, with percentage of nonoverlapping data (PND) at 72% and 75%, respectively, for quality and elements, indicating an effective treatment. Variations of the SRSD approach have been successfully used to improve the writing of children with learning disabilities (see Graham et al, in press), students with emotional and behavioral disorders (Mason, Kubina, Valasa, & Cramer, 2010;Mastropieri et al, 2009) and attention deficit hyperactivity disorder (ADHD; Reid & Lienemann, 2006), and most recently children with ASD (cf. Asaro-Saddler & Bak, 2012;Asaro-Saddler & Saddler, 2010;Delano, 2007aDelano, , 2007b.…”
Section: Srsdmentioning
confidence: 99%